2005
DOI: 10.1002/ceat.200500036
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Kinetics of Fischer‐Tropsch Reaction on Iron Based Catalysts and Product Grade Optimization

Abstract: The polymerization kinetics of Fischer-Tropsch reactions on a K-promoted Fe catalyst was studied. To represent the product distribution, a kinetic model was developed based on alkyl and alkenyl mechanisms for hydrocarbon chain propagation, which were assumed to occur simultaneously in the Fischer-Tropsch synthesis. The conclusion was drawn that superimposed Anderson-Schulz-Flory (ASF) distributions with different chain growth probabilities, on iron catalysts, can be the result of different chain growth mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
(11 reference statements)
1
18
0
Order By: Relevance
“…On the other hand, lower temperature is preferential for chain growth and the production of heavy hydrocarbons [42]. It was reported that at lower reaction temperatures the conversion percentage of CO is low [43,2]; Fernandes reported that temperatures lower than 180 8C may not provide enough energy to active the reagents on the catalyst, and the reaction may not over begin [44].…”
Section: Effect Of Reaction Temperaturementioning
confidence: 98%
“…On the other hand, lower temperature is preferential for chain growth and the production of heavy hydrocarbons [42]. It was reported that at lower reaction temperatures the conversion percentage of CO is low [43,2]; Fernandes reported that temperatures lower than 180 8C may not provide enough energy to active the reagents on the catalyst, and the reaction may not over begin [44].…”
Section: Effect Of Reaction Temperaturementioning
confidence: 98%
“…The model has been validated using the data reported by Raje and Davis1 and Donnelly and Satterfield21 and has provided a satisfactory fitting20 (samples are shown in Figure 1). Variance analysis was done using the software Statistica 6.0 which showed that the model is significant within 1% of confidence.…”
Section: Mathematical Modelmentioning
confidence: 83%
“…The population balance for the FTS species are given by the following set of equations The development of the population balances assumes that the quasi‐steady state is applied to the propagating species (as commonly assumed for the moments of live polymers); the consumption of methylene units is proportional to the overall reaction rate; and the concentration of hydrogen in the polymerization site is proportional to the partial pressure of hydrogen in the reaction media. The details on the development of the population balances for the FT synthesis for this specific catalyst (Fe:0.005K:21.7Si) can be found in Fernandes20. The kinetic parameters for the CO polymerization are presented in Table 5.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The mathematical model used in the program was described and presented in Fernandes (2005). The resulting differential system of equations is solved by numerical integration using a 5 th order Runge-Kutta method (Hull et al, 1976).…”
Section: Simulation Modelsmentioning
confidence: 99%